Improvement of Trimethylamine Uptake by Euphorbia milii: Effect of Inoculated Bacteria - Dian Siswanto; Paitip Thiravetyan (Journal of Tropical Life Science, 2016)
In the last few years, a great emphasis has been placed on phytoremediation of indoor air pollution studies. However, limited work has been addressed to observe the bacteria potential to assist the phytoremediation process of trimethylamine (TMA). In this work, the ability of 4 different bacteria for individual TMA removal and IAA production were observed. In addition, the enhancement of TMA removal efficiency by Euphorbia milii with various inoculating bacteria were investigated. Bacillus thuringiensis, Citrobacter amalonaticus Y19, Bacillus nealsonii, and white colony-soil bacteria (WCSB) were able to absorb TMA and produce IAA individually. B. thuringiensis and C. amalonaticus Y19 were the two most effective bacteria to improve TMA removal efficiency by the plant. Since concentrations of IAA production by individual bacterium were highly correlated with TMA removal efficiency by plants in early periods of fumigation and highly correlated with leaf IAA production of bacterially inoculated plants, two predicted mechanisms on improving TMA uptake by bacterially inoculated plants are presented: (1) bacteria migration from plant roots to leaves increases leaf IAA concentration and (2) increasing concentration of bacterially inoculated root IAA inhibits transportation of IAA from leaves to roots, resulting in higher leaf IAA concentration. The higher concentration of leaf IAA is suggested to be a factor to increase stomatal opening which improves TMA removal efficiency of the plant.